Field-Free Line Magnetic Particle Imaging Magnet Design Using Nested Halbach Cylinders - Ergor, Melike; Bingolbali, Ayhan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Magnetic particle imaging (MPI) is a novel imaging technique that is a promising candidate for practical use in the medical field. The field-free line (FFL) selection field method in MPI provides spatial encoding along a line, resulting in a faster acquisition time and enhanced sensitivity with increased signal-to-noise ratio. To obtain FFL, a magnet system was designed using nested Halbach rings with octagonal-shaped permanent magnets. In this specific study, simulation studies were implemented using this magnet system for a real case. For this purpose, gradient values and stabilities of the magnet system were calculated. In this investigation, a gradient field within 60 mm stability was obtained along each axis. The gradient field attained values up to 6.1 T/m, which is a highly important parameter for spatial resolution in MPI systems.
Keywords: Magnetic resonance imaging; Magnetic particle imaging; Imaging; Magnetic flux density; Permanent magnets; Solid modeling; Magnetization; Hard magnetic materials; field-free line; Halbach magnets; gradient field; Engineering; Physics